Analisis Kepuasan Pelanggan dalam Layanan Distribusi Pengiriman Barang pada J&T Express Lotu Kabupaten Nias Utara - Zega, Aperianto; Telaumbanua, Aferiaman; Gea, Nov Elhan; Gea, Jeliswan Berkat Iman Jaya (Jurnal EMT KITA, 2025)
The purpose of the study is to determine Customer Satisfaction with Goods Delivery Distribution Services and to determine the inhibiting factors in goods delivery distribution services at J&T Express Lotu, North Nias Regency. The research method used is a qualitative research type using data collection techniques, namely observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study indicate that Customer Satisfaction with goods delivery distribution services at J&T Express Lotu still faces various challenges. The main factors that influence customer satisfaction include punctuality of delivery, quality of service, transparency of information in the delivery process, variety of services available, and communication between customers and service officers. There are several inhibiting factors that cause customer dissatisfaction with distribution services at J&T Express Lotu. The first factor is late delivery, quality of service, lack of transparency in the delivery process, limited variety of services, lack of communication between customers and service officers.